Efficient Tool for the Recognition of the Leaves of Plants, ISSN 1694-0814 - Abdelhadi Adel; Mouss Leila Hayet; Mahdaoui Rafik (IJCSI International Journal of Computer Science Issues, 2012)
This work appears in pattern recognition in the agronomic domain, especially for the identification of the leaves of plants, while using the adaptive technique of neuronal networks. In this article, we will expose our tool; which is intended for two categories of specialists, the first consisting of researchers in the field of botany, as the second, so all scientists, who may use this work in their own applications. We will expose also, the capacities of generalization of the neuronal networks and their implementation to our problem